Perancangan Tatanan Lahan di Pusat Hewan dan Shelter Kucing dengan Tema Arsitektur Bioklimatik - Luky Dwi Sasmita (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
Surabaya has a population of wild and domesticated animals that is increasing every year plus more and more communities of pet owners of both racial and domestic types. As well as the existence of an animal contest for the gathering of animal owners into a community business opportunity in the trade sector. Therefore, people in Surabaya need a place or center for animal needs that provides a complete range of goods and services. The theory used in this paragraph is Contemporary Bioclimatic Architecture (Yeang) which is an energy-efficient design method that takes into account the local climate and solves climate problems by applying it to building elements. The macro concept applied to the design is a comfortable building with open space as well as a micro concept of land arrangement in response to nature, a solid building form with the use of modern materials and a room connected to nature.From the results of the application of the concept, the results of the design of the land structure with an organic pattern appear where the configuration of the building mass and space around the balance axis is straight to the building. Then the modern building form has contemporary characteristics with rooms that are connected to nature in terms of the materials used, and the placement of openings so that air and light circulation is maximized.